2022
DOI: 10.1126/sciadv.abn9699
|View full text |Cite
|
Sign up to set email alerts
|

Mitonuclear genotype remodels the metabolic and microenvironmental landscape of Hürthle cell carcinoma

Abstract: Hürthle cell carcinomas (HCCs) display two exceptional genotypes: near-homoplasmic mutation of mitochondrial DNA (mtDNA) and genome-wide loss of heterozygosity (gLOH). To understand the phenotypic consequences of these genetic alterations, we analyzed genomic, metabolomic, and immunophenotypic data of HCC and other thyroid cancers. Both mtDNA mutations and profound depletion of citrate pools are common in HCC and other thyroid malignancies, suggesting that thyroid cancers are broadly equipped to survive tricar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Cancer arises from genomic alterations that can lead to dysregulation of gene expression and drive oncogenesis within and across tumor types . Significant advances have been made in the understanding of cancer molecular pathogenesis, including genetic and epigenetic alterations . Molecular assays, such as real-time polymerase chain reaction (PCR) and next-generation sequencing (NGS), have arisen to detect genomic changes in tumors as novel cancer diagnostic approaches with great potential in the preoperative stratification of malignancy or benignity in thyroid nodules .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer arises from genomic alterations that can lead to dysregulation of gene expression and drive oncogenesis within and across tumor types . Significant advances have been made in the understanding of cancer molecular pathogenesis, including genetic and epigenetic alterations . Molecular assays, such as real-time polymerase chain reaction (PCR) and next-generation sequencing (NGS), have arisen to detect genomic changes in tumors as novel cancer diagnostic approaches with great potential in the preoperative stratification of malignancy or benignity in thyroid nodules .…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that ETC function was below a threshold required for viability following LDH inhibition or culture in glucose-free or galactose-containing media. Analysis of glucose metabolism in XTC.UC1 revealed that these cells display defects in glucose oxidation and recent profiling of patient-derived HTC tumors identified metabolic changes consistent with ETC dysfunction (Ganly et al ., 2022). Therefore, HTC tumors that lack damaging near-homoplasmic mtDNA mutations might harbor sufficient disruption of oxidative phosphorylation and glucose metabolism to be sensitized to LDH inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial accumulation and evidence of metabolic rewiring are defining features of HTC, yet approximately 40% of HTC tumors do not harbor discrete mutations in complex I subunits (Ganly et al, 2022; Ganly et al ., 2018; Ganly and McFadden, 2019; Gopal et al ., 2018; McFadden and Sadow, 2021). This raises the question whether all HTC tumors exhibit functional ETC impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of somatic copy number alterations suggest that the wide chromosome instability observed in OTC may be associated with altered DNA damage repair, possibly related to a metabolic reprogramming and imbalance of ROS intracellular levels . Interestingly, gLOH was found to be associated with a depletion in immune cell infiltration, indicating that gLOH could confer a selective advantage partially through suppression of cytotoxic immune responses …”
Section: Observationsmentioning
confidence: 99%